Comparison of Skeletal Muscle Changes at Three Vertebral Levels Following Radiotherapy in Patients With Oropharyngeal Carcinoma. (7th February 2023) - Vangelov, Belinda; Bauer, Judith; Moses, Daniel; Smee, Robert
Abstract: Evaluation of skeletal muscle (SM) depletion, or sarcopenia, utilizes the cross-sectional area (CSA) of computed tomography (CT) scans at the lumbar level L3. However, alternate vertebral landmarks are used in patients with head and neck cancer due to scan unavailability. Muscle changes following radiotherapy at cervical (C3) and thoracic (T2) levels were compared to L3 in patients with oropharyngeal carcinoma. Muscle density data were derived retrospectively from diagnostic PET-CT scans at C3, T2 and L3 pretreatment, and up to six months post. CSA changes were compared to L3 in scans of 33 patients (88% male, mean age 61 (SD 8.5) years). On matched pair analysis; mean L3-CSA change −12.1 cm 2 (SD 9.7, 95%CI −15.5 to −8.6, and p < 0.001), T2-CSA −30.5 cm 2 (SD 34.8, 95%CI −42.8 to −18.1, and p < 0.001) and C3-CSA +2.1 cm 2 (SD 4.1, 95%CI 0.63 to 3.5, and p < 0.00). No difference was found in the percentage change of T2-CSA with L3-CSA (mean −2.2%, SD 10.6, 95%CI −6.0 to 1.6, and p = 0.240), however, was significantly different to C3-CSA (mean 13.2%, SD 11.6, 95%CI 9.1 to 17.3, and p < 0.001). Results suggest SM at C3 does not change proportionately and may not be a reliable representation of whole-body SM change over time.